PENGARUH SOCIAL MEDIA, CONTENT MARKETING, DIGITAL MARKETING, BRAND AWARENESS, CUSTOMERS SATISFACTION TERHADAP PURCHASE INTENTION DI DALAM BISNIS MINUMAN KEKINIAN YANG DI MEDIASI OLEH TRUST DI KOTA BATAM - Hasan, Golan; Chang, Jesseline (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
This research was conducted with the aim of identifying and analyzing factors that influence purchase intentions in the beverage business. In this case, the object of this research is people in the city of Batam who know about the beverage business and have the intention to buy beverage business products. The independent variables used in the object of this research are social media, content marketing, digital marketing, brand awareness, and customer satisfaction. The intervening variable used is trust and the dependent variable used is purchase intention. This research uses a quantitative approach in data collection and a purposive sampling technique for data analysis using Smart PLS. The sample for this research was the community in the city of Batam with a total of 300 respondents. The results of this study show that there is an influence of social media (SM), content marketing (CM), digital marketing (DM), brand awareness (BA) and customer satisfaction (CS) on purchase intention (PI) which is mediated by trust (T) in Batam city. This research also indicates that trust (T) can significantly mediate the relationship between social media (SM), content marketing (CM), digital marketing (DM), brand awareness (BA) and customer satisfaction (CS) on purchase intention (PI).